An E2F1/DDX11/EZH2 Positive Feedback Loop Promotes Cell Proliferation in Hepatocellular Carcinoma - Su, Shu-Guang; Li, Qiu-Li; Zhang, Mei-Fang; Zhang, Peng-Wei; Shen, Huimin; Zhang, Chris Zhiyi (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) accounts for one of the leading causes of cancer-related death, and is attributed to the dysregulation of genes involved in genome stability. DDX11, a DNA helicase, has been implicated in rare genetic disease and human cancers. Yet, its clinical value, biological function and the underlying mechanism in HCC progression are not fully understood. Here, we show that DDX11 is upregulated in HCC and exhibits oncogenic activity via EZH2/p21 signaling. High expression of DDX11 is significantly correlated with poor outcomes of HCC patients in two independent cohorts. DDX11 overexpression increases HCC cell viabilities and colony formation, whereas DDX11 knockdown arrests cells at G1 phase without alteration of p53 expression. Ectopic expression of DDX11 reduces, while depletion of DDX11 induces the expression of p21. Treatment of p21 siRNA markedly attenuates the cell growth suppression caused by DDX11 silence. Further studies reveal that DDX11 interacts with EZH2 in HCC cells to protect it from ubiquitination-mediated protein degradation, consequently resulting in the downregulation of p21. In addition, E2F1 is identified as one of the upstream regulators of DDX11, and forms a positive feedback loop with EZH2 to upregulate DDX11 and facilitate cell proliferation. Collectively, our data suggest DDX11 as a promising prognostic factor and an oncogene in HCC via a E2F1/DDX11/EZH2 positive feedback loop.